Changes in brain structure in subjects with resistance to thyroid hormone due to THRB mutations - Berenike Rogge; Marcus Heldmann; Krishna Chatterjee; Carla Moran; Martin Göttlich; Jan Uter; Tobias A. Wagner-Altendorf; Julia Steinhardt; Georg Brabant; Thomas F. Münte; Anna Cirkel (Thyroid Research, 2023)
Abstract Background Being critical for brain development and neurocognitive function thyroid hormones may have an effect on behaviour and brain structure. Our exploratory study aimed to delineate the influence of mutations in the thyroid hormone receptor (TR) ß gene on brain structure. Methods High-resolution 3D T1-weighted images were acquired in 21 patients with a resistance to thyroid hormone ß (RTHß) in comparison to 21 healthy matched-controls. Changes in grey and white matter, as well as cortical thickness were evaluated using voxel-based morphometry (VBM) and diffusion tensor imaging (DTI). Results RTHß patients showed elevated circulating fT4 & fT3 with normal TSH concentrations, whereas controls showed normal thyroid hormone levels. RTHß patients revealed significantly higher scores in a self-rating questionnaire for attention deficit hyperactivity disorder (ADHD). Imaging revealed alterations of the corticospinal tract, increased cortical thickness in bilateral superior parietal cortex and decreased grey matter volume in bilateral inferior temporal cortex and thalamus. Conclusion RTHb patients exhibited structural changes in multiple brain areas. Whether these structural changes are causally linked to the abnormal behavioral profile of RTHß which is similar to ADHD, remains to be determined.